Synthesis of thin film composite forward osmosis membranes - Liau, Wei Min. (2011)
Forward Osmosis (FO) technology is becoming popular due to its potential applications in many important fields and its numerous advantages. One major challenge of FO is internal concentration polarization (ICP). It limits the efficiency of FO flux. There is a lack of effective FO membrane with low ICP propensity. Thus high performance FO membrane of a better quality is required. Therefore high performance FO membranes were prepared. In this project, thin film composite (TFC) polyamide FO membranes had been fabricated. The porous polysulfone support layer of the membrane was casted by phase inversion, and its active rejection layer was synthesized on top of the support layer through interfacial polymerization. As a result the structural parameter achieved by the fabricated membrane TFC-1was found to be 0.71mm. Comparison of the fabricated FO membranes to the commercial FO and RO membranes demonstrates the critical importance of each layer .FO membranes of having a highly porous substrate layer have straight finger like pores than sponge-like pore structure, are able to minimize the effect of concentration polarization. The active rejection layer of TFC-1 had also shown superior separation properties than commercial FO membranes. High water permeability rate and high NaCl rejection were achieved. Optimizations were also made to both support layer and the rejection layer of the membranes. TFC-2 had a better rejection layer than TFC-1. TFC-2 had achieved a higher water permeability rate of 5x10-12 m/s.Pa and a better water flux rate in FO. TFC-3 with an improved substrate, had the smallest structural parameter of 0.42mm which greatly contributes to its water flux being higher than TFC-2 even when the membrane rejection layer was orientated to the feed solution.